2022
DOI: 10.1073/pnas.2214941119
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of acetyl-CoA-based products via peroxisomal surface display in Saccharomyces cerevisiae

Abstract: Colocalization of enzymes is a proven approach to increase pathway flux and the synthesis of nonnative products. Here, we develop a method for enzyme colocalization using the yeast peroxisomal membrane as an anchor point. Pathway enzymes were fused to the native Pex15 anchoring motif to enable display on the surface of the peroxisome facing the cytosol. The peroxisome is the sole location of β-oxidation in Saccharomyces cerevisiae, and acetyl-CoA is a by-product that is exported in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
(58 reference statements)
0
14
0
Order By: Relevance
“…TAL is also regarded as a platform chemical capable of being converted into a wide range of high-value and commodity products . In recent years, the TAL of high titers has been produced in several heterologous hosts, including E. coli ; , S. cerevisiae ; , and nonconventional yeasts, such as Yarrowia lipolytica , Rhodotorula toruloides , and Kluyveromyces marxianus , , after the introduction of the g2 ps-1 gene, which engineers the enzyme or rewires endogenous metabolic pathways. In all of the studies above in yeasts, TAL was exclusively synthesized in the cytosol by engineering cytosolic acetyl-CoA and malonyl-CoA supply, and TAL production was further enhanced by decreasing the carbon flux into mitochondrial acetyl-CoA. ,, In a very recent study, a three-enzyme metabolon displayed on the peroxisomal outer surface captured peroxisomal acetyl-CoA transported to the cytosol (in the form of acetyl-carnitine), which increased cytosolic TAL synthesis by more than 10-fold over the starting strain .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TAL is also regarded as a platform chemical capable of being converted into a wide range of high-value and commodity products . In recent years, the TAL of high titers has been produced in several heterologous hosts, including E. coli ; , S. cerevisiae ; , and nonconventional yeasts, such as Yarrowia lipolytica , Rhodotorula toruloides , and Kluyveromyces marxianus , , after the introduction of the g2 ps-1 gene, which engineers the enzyme or rewires endogenous metabolic pathways. In all of the studies above in yeasts, TAL was exclusively synthesized in the cytosol by engineering cytosolic acetyl-CoA and malonyl-CoA supply, and TAL production was further enhanced by decreasing the carbon flux into mitochondrial acetyl-CoA. ,, In a very recent study, a three-enzyme metabolon displayed on the peroxisomal outer surface captured peroxisomal acetyl-CoA transported to the cytosol (in the form of acetyl-carnitine), which increased cytosolic TAL synthesis by more than 10-fold over the starting strain .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we showed that peroxisomes provide an additional acetyl-CoA reservoir and extra space to accommodate enzymes so that utilization of the peroxisomal pathway plus the cytosolic pathway produces more polyketide than using the cytosolic pathway alone. Therefore, the strategy of using peroxisomal acetyl-CoA in situ can be considered as an alternative strategy to using peroxisomal acetyl-CoA by yeast peroxisome surface display …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BY_TEFnbit was created from BY4741 using donors amplified from pXP318-Cse3-SmBiT and pXP318-Csy4-LgBiT targeting sites XI-3 and XI-5, respectively. BY4741VioAB was previously created in the laboratory by integrating the donor generated from TEF1p-VioA-CYC1t and TEF1p-VioB-CYC1t into sites XI-3 and XI-5 . Donor fragments amplified from pXP318-cse3-VioE and pXP318-csy4-VioC were integrated into strain BYVioAB at sites X-2 and XII-4 to create strain BYVioAB3E4C.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid DNA (1 μg) was used for routine yeast transformation. For CRISR/Cas9 gene integration, the Cas9 plasmid was transformed into the yeast strains first before the strains were cotransformed with 1 μg of gRNA plasmid DNA and 1–2 μg of donor DNA. The samples were plated onto an appropriate selective plate and incubated at 30 °C for 3–5 days for single colonies to form.…”
Section: Methodsmentioning
confidence: 99%